Adolescents' responses to the distress of others: The influence of multiple attachment figures via empathic concern. (May 2021) - Profe, Wade B.; Wild, Lauren G.; Tredoux, Colin
Attachment theory provides an informative theoretical description of how prosocial behaviors in response to the distress of others may be socialized. This study aimed to investigate associations between attachment security to mothers, fathers, closest grandparents and peers, and young adolescents' (a) prosocial responses to others' distress and (b) global prosocial behaviors, via the mediation of empathic concern. Cross-sectional survey data were obtained from 520 adolescents (aged 11–14) from nine schools in Cape Town, South Africa. Structural equation modeling revealed that a model in which all paths from the attachment variables were routed through empathic concern was superior to a model which proposed only direct effects of attachment on prosocial behavior. Peer and grandparent attachment were significantly associated, through empathic concern, with self-reported helping in response to others' distress. For teacher-reported global prosocial behavior, the indirect effects of peer and grandparent attachment failed to reach significance. The results provide theoretical insight into the association between secure attachments and prosocial behavior, and highlight the importance of relationships with friends and grandparents in early adolescence.